What is gender awareness in health? A scoping review of the concept, its operationalization, and its relation to health outcomes - Morais, R.; Bernardes, S. F.; Verdonk, P. (Women and Health, 2022)
Gender awareness emerged in the 1990s and aimed to provide awareness and sympathy toward the needs of women, measuring health-care providers’ attitudes toward them and understand if providers possessed the knowledge for appropriate care. According to Miller et al.’s seminal model, gender awareness incorporates three sub-dimensions: gender sensitivity, gender ideology, and knowledge. Gender awareness has the potential to minimize gender bias in health care, improving the ecological validity of research. This scoping review provides an analysis of how gender awareness has been conceptualized, operationalized, and investigated in its relationship with health-related outcomes. A search was conducted on PubMed, PsycINFO, and ERIC. The relevance of 2.589 articles was assessed and 14 empirical studies were selected and included. Difficulties conceptualizing gender awareness were found and gender awareness and gender sensitivity were often presented as interchangeable. Most papers aimed to measure and compare levels of gender awareness among health professionals and the relationship between gender awareness and relevant health-related outcomes was not studied. Drawing upon a critical analysis of our findings, a proposal for a revised gender awareness conceptualization and operationalization is put forth as to inform novel research on its association with gender bias in health and health care.